The Success of Sharia Microfinance in Encouraging MSMEs (International Journal of Economics Management and Social Science, 2026)
This study aims to describe the success of Sharia Microfinance in encouraging the development of Micro, Small, and Medium Enterprises (MSMEs). The research method used is qualitative with a descriptive approach, through in-depth interviews and observations of MSMEs and Sharia Microfinance managers in certain areas. The results show that Sharia Microfinance is able to provide access to financing in accordance with Sharia principles, increase MSME business capacity, and strengthen the social and economic aspects of business actors. This success is influenced by aspects of trust, transparency, and social support from Sharia financial institutions. These findings confirm that Sharia Microfinance has great potential in supporting the sustainable growth of MSMEs, particularly through the application of Sharia principles that balance economic and social aspects. This study recommends that the development of Sharia Microfinance be continued through product innovation and increasing the capacity of managers to encourage more inclusive and sustainable MSME growth.